Guidebook for developing and leasing airport property - Crider, Rick (Transportation Research Board, 2011)
ACRP report 47 explores issues associated with developing and leasing available airport land and summarizes best practices from the perspective of the airport sponsor. The guidebook includes a diverse set of case studies that show several approaches airports have taken to develop and lease property for both aeronautical uses and non-aeronautical uses. The project that developed the guidebook also produced two presentation templates designed to help airports in effective stakeholder communication regarding developing and leasing airport property. The templates, designed for a non-technical audience, provide content, examples, and definitions for a presentation to community stakeholders. The templates, one for aeronautical use development presentations, and the second for non-aeronautical use development presentations are available only online.
At head of title: Airport Cooperative Research Program.
"Research sponsored by the Federal Aviation Administration."
Keywords: Airports -- United States -- Management.; Real estate development.; Leases.; Land use.; United States.; elektronické knihy; electronic books